Psychological inoculation against problematic social media use among adolescents: An experimental study - Sameha Alshakhsi (17032311) (2025)
This research investigated whether an attitudinal inoculation intervention can build resistance against problematic social media use (PSMU) in adolescents. This experimental study assessed PSMU levels and attitudes toward PSMU before and after the intervention. The intervention utilized scenarios reflecting symptoms of PSMU, including preoccupation, tolerance, withdrawal, persistence, displacement, problem, deception, escape, and conflict. Scenarios employed Cialdini's persuasion principles (reciprocity, liking, social proof, scarcity, authority, and commitment and consistency) and explained these principles to participants. The study included a control group, active inoculation group (participants identified countermeasures to PSMU scenarios), and passive inoculation group (countermeasures were provided). Participants were adolescents aged 11–15 years. A mixed ANCOVA was employed to test the intervention's impact on PSMU, post‐intervention attitude changes, and post‐inoculation talk (PIT) about excessive technology use. Results indicated a significant decrease in PSMU levels following active inoculation, particularly in withdrawal, persistence, displacement, and deception symptoms. The passive inoculation group showed a significant decrease in deception only. No changes were observed in the control group. Regarding PIT, passive inoculation showed a marginally significant increase in negative PIT, whereas active inoculation saw a slight reduction in positive PIT. These findings, while exploratory, suggest attitudinal inoculation's potential for mitigating PSMU and warrant further research. Other Information Published in: Annals of the New York Academy of Sciences License: http://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.1111/nyas.70011